Application of the ADDIE Model in the Development of an Android-Based Physics Quiz Game - Andryanto Aman; Tamra Tamra; Ramlah Ramlah; Andi Ridwan Makkulawu (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Conventional physics instruction in junior secondary schools often struggles to maintain student interest, leading to disengagement and diminished comprehension. This research details the application of the ADDIE model to design and develop an Android-based physics quiz game intended as a supplementary learning tool to address this issue. The study utilised a Research and Development (R&D) methodology, systematically progressing through the model's five distinct phases: Analysis, Design, Development, Implementation, and Evaluation. The initial analysis involved literature reviews and field studies at SMP Negeri 17 Makassar to identify specific learning requirements. Following the development and implementation phases, the application was assessed for its functionality and user reception through a quantitative User Acceptance Test (UAT). The key finding of this research was an overall acceptance score of 86% from student participants. This significant result confirms that the developed game not only functions correctly but is also perceived by students as an engaging and effective educational resource, validating its potential to enhance the learning process in physics.